Mapping of land degradation using spectral angle mapper approach (SAM): the case of Inaouene watershed (Northeast Morocco) - Benzougagh, Brahim; Meshram, Sarita Gajbhiye; Fellah, Bouchta El; Mastere, Mohamed; Basri, Mohamed El; Ouchen, Ibrahim; Sadkaoui, Driss; Bammou, Youssef; Moutaoikil, Nassima; Turyasingura, Benson (Springer Nature Switzerla, 2023)
Soil erosion is one of the most critical hazards adversely afecting both environment and economy for all countries in the world. Several regions of Morocco sufer from the problem of soil erosion, notably the Rif and the Pre-Rif where the study area of this paper is located. The spectacular expansion of soil erosion processes in the Lahdar watershed is a worrying indicator of soil degradation. Geographic information systems and remote sensing are an excellent tool for analyzing and evaluating the risks of the expansion of soil degradation. The main objective of this paper is to assess spectral angle mapper (SAM) method and analyze their properties using geographic information system and image processing techniques in order to map the hazards of soil erosion. Land use and land cover dynamics demonstrate the relationship between human-induced development and the evolution of soil degradation and biodiversity conservation in a watershed. Therefore, an understanding of LULC factors is required for the implementation of environmental policies intended to foster a synergy between humans and the sustainability of their environment. The process of categorizing LULC was completed using the SAM technique, and the role of LULC in the dynamics of soil degradation was investigated using measurements of landscape fragmentation. For this purpose, Landsat 8 Operational Land Imager data (11 bands) with 30-m spatial resolution, 22 August –2017 were used, and classifers for SAM were applied and evaluated. The fndings of the study are seven main land cover categories: arboriculture (0.08%), cereal (35.05%), water (1.03%), forests (3.76%), residentials (4.61%), matorral-course (4.58%), and bare soils (50.89%). It should be noted that the bare soil class occupies half of the watershed area, making it vulnerable to the risks of soil degradation. Moreover, the results from this study will aid decision makers in better conservation planning of soil and water resources.